DAMPAK KEBIJAKAN FISKAL TERHADAP STABILITAS EKONOMI PASCA PANDEMI COVID-19 - Lamali, Dani Irfan A.; Hasim, Hasim (JAMBURA: Jurnal Ilmiah Manajemen dan Bisnis, 2026)
This study aims to analyze the impact of fiscal policy on Indonesia’s economic stability in the post-COVID-19 period. Fiscal policies in this context include government spending, tax revenues, and budget deficit management implemented to support national economic recovery. The research employs a descriptive quantitative approach, using secondary data obtained from the Central Bureau of Statistics (BPS), the Ministry of Finance, and Bank Indonesia for the period 2020 2024. The results indicate that expansionary fiscal policies, particularly through increased government expenditure and tax incentives, have played a significant role in stimulating economic growth, reducing unemployment, and maintaining household purchasing power. However, the widening budget deficit and rising public debt have also created potential risks to long-term macroeconomic stability. Overall, post-pandemic fiscal policies have proven effective in maintaining short-term economic stability, although a sustainable fiscal consolidation strategy is required to ensure long-term financial resilience.